Female education in Iraq 1921-1958 - A historical Study- (Journal of the College of Education for Women, 2019)
In spite of the foundation of Iraqi state in 1921 and the formation of the new features ofthe modern state, however, the inherited costumes and traditions sustained in the conservativesociety. But due to the development that inflicted to the Iraqi society and the development ofthe staff in all fields and requirement conducting to female learning. After WW II and the1950s, women get out of their houses to seek learning by approaching the doors.What is positive about that phase was the formation of the College of Queen A'liyawhich is regarded as a positive indicator. In any case the Iraqi family encouraged women tobe indulged in higher education. Calling the college Queen A'liya